2020
DOI: 10.3389/fpls.2020.621859
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Brassinosteroid Signaling and Salt Resistance by SERK2 and Potential Utilization for Crop Improvement in Rice

Abstract: The complex roles of the steroid hormone brassinosteroids (BRs) in many different yield- and stress-related traits make it difficult to utilize the hormones for crop improvement. Here, we show that SERK2 as a BR signaling component is a potentially useful candidate for BR manipulation in rice. We generated multiple mutant alleles of SERK2 by CRISPR/Cas9 editing and show that knockout of SERK2 results in a compact structure accompanied with increased grain size. SERK2 is localized on plasma membrane and can int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
(48 reference statements)
0
20
0
1
Order By: Relevance
“…The BR receptor SERK2 significantly enhances grain size and salt resistance in rice. Adverse high salinity conditions induce SERK2 accumulation to enhance early BR signaling on the plasma membrane to defend against the stress [ 85 ].…”
Section: Regulation Of Plant Response To Salt Stressmentioning
confidence: 99%
“…The BR receptor SERK2 significantly enhances grain size and salt resistance in rice. Adverse high salinity conditions induce SERK2 accumulation to enhance early BR signaling on the plasma membrane to defend against the stress [ 85 ].…”
Section: Regulation Of Plant Response To Salt Stressmentioning
confidence: 99%
“…Various BR signaling components manipulate the BRs, resulting in multiple responses. In rice, Somatic embryogenesis receptor kinase 2 ( SERK2 ) expression is enhanced under salt stress, which eventually activates BR signaling, thereby improves salt tolerance (Dong et al, 2020). BRs are reported to regulate MAPK signaling to decrease the stomatal conductance, thereby improving salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in rice, knockout of SERK2 , a BR signaling component, showed enhanced salt sensitivity. However, the overexpression of SERK2 resulted in improved salt resistance and enhanced grain size without influencing the rice seedling architecture (Dong et al, 2020). Thus, manipulating the BR signaling by overexpressing SERK2 improved growth in rice under salt stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in red mango fruit, RNA-seq analysis suggested that the genes involved in the brassinosteroid signaling pathway were upregulated and increased plant resistance to light 46 . In addition, in brassinosteroid signaling, SERK2, as a BR signaling component, could interact with OsBRI1 to promote early BR signaling and enhance grain size and salt tolerance 47 . Therefore, flavonol biosynthesis and BR signaling have important functions in plant resistance, and during this process, ROS act as plant signals to respond to environmental changes 48 .…”
Section: Discussionmentioning
confidence: 99%